Komunikasi End of Life dengan Penyusunan Dokumen Wasiat Hidup: Qualitative Evidence Synthesis - Wahyuni, Jathu Dwi; Yetti, Krisna; Gayatri, Dewi; Rachmawati, Imami Nur; Meidiawati, Ati Surya (Faletehan Health Journal, 2023)
End of Life (EoL) communication is carried out when the patient's condition is palliative and documented in an advance Directives (ADs) document which contains of patient's preferences of treatment options. ADs are highly important documents for patients, families and health worker, but have not been applied in Indonesia. This study aimed to identify the stages of preparing ADs with qualitative evidence synthesis research design. The Data sources used several data bases, namely Sage Journals, ProQuest, Scopus, Taylor & Francis, ScienceDirect, and ClinicalKey Nursing from 2003 to 2023. The article selection was based on the category of qualitative research on EoL communication and ADs drafting. The results of the study obtained 6 out of 38,185 articles. The articles contained of the stages of preparing ADs starting with the initiation of patients or health workers, providing an explanation of ADs and the course of patient's disease, discussion or EoL communication between families and health workers, reviewing the decisions in ADs according to patient's condition, and making ADs according to local regulations. The researchers concluded that ADs document as the result of EoL communication should be made by health workers and patients. ADs document is important for patients, families and health workers and can help patients become calmer to face a follow-up care and end-of-life care.